The Men’s Marriage Premium in the United States: What Remains after Controlling for Publication Bias and Heterogeneity? - Nuwan Indika Millagaha Gedara (Colombo Business Journal, 2021)
Married men earn more than single men, which is a significant finding in labour and family economics. A considerable amount of research literature discusses this estimated wage effect for married men in the United States. This study finds a meaningful impact on wage after controlling for the publication bias with heterogeneity, a considering meta-analysis of 120 estimates. Marriage premium accounts for 6.8% compared to unmarried men with the evidence of publication bias after applying descriptive statistics, funnel graph, simple meta-regression analysis (MRA), and multiple MRAs. Also, this analysis identifies omitted variable bias as another important aspect for explaining this widespread empirical literature.